Confocal interferometric scattering microscopy reveals 3D nanoscopic structure and dynamics in live cells - Michelle Küppers; David Albrecht; Anna D. Kashkanova; Jennifer Lühr; Vahid Sandoghdar (Nature Communications, 2023)
Label-free imaging is crucial to life sciences, but it can be hampered by the lack of 3D imaging capability and low nanoscopic sensitivity. Here, authors show a confocal interferometric scattering microscopy approach allowing the quantification of nanometric topography and intracellular dynamics.